MODEL PENINGKATAN PENERIMAAN PAJAK MINERAL BUKAN LOGAM DAN BATUANDI KABUPATEN KUBU RAYA - B61112007, ALI AMIN (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT This study titled "The Methodeof Tax Increased Acceptance of Non Metallic Minerals and Rocks Tax at Kubu Raya Regency,Â  is a case study in Kubu Raya Regency. The aim of studi is to analyze the potential and effectiveness of tax collection it, and make a methode or strategy in improving tax revenue of nonmetallic minerals and rocks at Kubu Raya Regency. The method used is descriptive research with qualitative and quantitative analysis. The qualitative analysis was carried out of existing conditions and potential as well as to the qualitative variables include collection process, of registration and inventing of tax. The quantitative analysis used to calculate the potential (capacity/quantity of sand) and real tax. The data used is primary and secondary data from observations,interviews and reports by DPPKAD (Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah). The results of this study are: (1) The effectiveness based on the ratio of actual and the target in 2010 and 2013 a very high average of over 100%. Targets set of DPPKAD too low, proved the effectiveness of the results of a calculation based on the real potential of 18 sand miners less than 100%. That is the potential that can be extracted only still below the real potential. 2) There is a difference in the calculation of the production capacity of the research results set by DPPKAD. 3) The strategy/policies Â formulated to increase revenue of itâ€™s tax are: (a) Data Collection and Registration of taxpayers do include licensing, NPWP, mining location, collaboration with relevant agencies (dinas kehutanan perkebunan dan pertambangan) as well as the involvement of village heads, heads of â€œRTâ€ until the Planning Agency. (b) In determining the tax rate for volume measurement production, pricing, output frequency, use SPTPD and annual tax return. (c) The collection of taxes by the SSP(billing), direct payments to the Treasury (Bank of West Kalimantan), (d) To maintain continuity of production supervision: production, waste, disaster/environmental damage, Revolution (water, air, natural) by Dinas Kehutanan Perkebunan Pertambangan, local government and the general public. Keywords: mineral taxes, data collection, registration, potency, effectiveness, policy.